2013
DOI: 10.4084/mjhid.2013.037
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in Combination With Dexamethasone in Elderly Patients With Advanced, Relapsed or Refractory Multiple Myeloma and Renal Failure

Abstract: Salvage therapy of elderly patients with advanced, relapsed and refractory multiple myeloma (MM) is often limited by poor marrow reserve and multi-organ impairment. In particular, renal failure occurs in up to 50% of such patients, and this can potentially limit the therapeutic options. Both thalidomide and bortezomib have proven effective in these patients, with an acceptable toxicity, while, in clinical practice, lenalidomide is generally not considered a first-choice drug for MM patients with renal failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our cohort consisted of consecutive, unselected patients treated at a single center, all of whom received similar supportive care. Consequently, we found that dose-adjusted Len plus low-dose Dex improved the renal function in the older RRMM patients with RI, as previously described (16).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our cohort consisted of consecutive, unselected patients treated at a single center, all of whom received similar supportive care. Consequently, we found that dose-adjusted Len plus low-dose Dex improved the renal function in the older RRMM patients with RI, as previously described (16).…”
Section: Discussionsupporting
confidence: 86%
“…Several other studies have tested the efficacy of Len combined with Dex in RRMM patients with RI, including Len adjusted for the renal function (6,9,18,19). With the exception of one study (16), however, all of the patients received a dose of >80 mg of Dex per cycle, which may increase the risk of severe infections in older RRMM patients with RI.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that with careful monitoring and with appropriate dose adjustments, lenalidomide could be used for relapsing or refractory MM in patients requiring dialysis. Overall, the results of studies to date indicate that lenalidomide therapy is an important treatment option in the management of MM in patients with RI [101,102,103,104,105]. …”
Section: Treatment Of Myelomamentioning
confidence: 99%
“…Several studies have assessed the role of treatment combinations based on bortezomib, thalidomide, and lenalidomide in newly diagnosed young and elderly patients as well as in those with relapsed/refractory disease [25][26][27][28][29][30][31] with different degrees of renal impairment.…”
mentioning
confidence: 99%